Need, justice and central–local relations: The case of social assistance in China - Li, M; Walker, R (Wiley, 2020)
Social assistance is increasingly promoted as a means of tackling poverty. However, in established democracies stable delivery has often proved difficult because of tensions between national and local government, the former desiring comprehensiveness and uniformity, the latter requiring flexibility to meet local needs. These issues are explored in the context of China and Dibao, the world's largest social assistance system, with three questions posed: Do similar tensions exist in China as in the Western world? How are they resolved and what is the nature of the political compromise? How do recipients fare? Policy analysis in a village in south-central China reveals similar tensions. A regime in which local government employed discretion to prioritize social stability over poverty alleviation has been replaced by an inherently unstable system based on surveillance of officials and local cadres who now prioritize their personal security over the needs of applicants.